2020
DOI: 10.1044/2020_lshss-19-00036
|View full text |Cite
|
Sign up to set email alerts
|

Using Parallel, Narrative-Based Measures to Examine the Relationship Between Listening and Reading Comprehension: A Pilot Study

Abstract: Purpose The purpose of this pilot study was to determine whether parallel measures of narrative-based listening comprehension and reading comprehension reflected the same construct and yielded comparable scores from a diverse sample of second- and third-grade students. One hundred ten students participated in this study. Method Three listening and three reading comprehension narrative retells and subsequent responses to story questions and vocabulary qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…The twoparameter logistic model as the adequate model fit was applied in this study. Approaches for assessing parallelism comprise the same construct, the equal reliability, the indifferent means and standard deviations, and the equal parameter estimates (Petersen et al, 2020). The statistical parallelism was investigated into three levels, including test sets, test forms, and item pairs as follows:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The twoparameter logistic model as the adequate model fit was applied in this study. Approaches for assessing parallelism comprise the same construct, the equal reliability, the indifferent means and standard deviations, and the equal parameter estimates (Petersen et al, 2020). The statistical parallelism was investigated into three levels, including test sets, test forms, and item pairs as follows:…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the advantages of the of IRT are invariance properties, a person parameter and an item parameter. IRT can be estimated from different samples onto a common scale, and test scores of different test forms are comparable to each other (Davey & Hendrickson, 2010;De Champlain, 2010;Hambleton & Jones, 1993) The use of parallel forms for repeated measure are generally preferred for intervention in classroom as one of the criteria for outcome measure (Petersen et al, 2020). The key advantages of the properly developed parallel forms result in fairness and security of a test (Bae & Lee, 2011;Clause et al, 1998;Lin, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A child's ability to successfully produce a narrative is an important developmental milestone for school-age children (Hughes et al, 1997). As narratives are complex in nature, they can be used as a measure of language ability throughout development (Hudson and Shapiro, 1991;Hughes et al, 1997;National Governors Association Center for Best Practices and Council of Chief State School Officers, 2010;Ukrainetz, 2015;Petersen et al, 2020). Many studies have discussed the usefulness of a schema theory-based approaches which employ measurement of SGEs to examine narrative ability (Stein and Glenn, 1979;Merritt and Liles, 1987;Berman and Nir-Sagiv, 2007;Bitetti and Hammer, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Some reading comprehension measures, for example, with multiple choice questions to assess literal understanding may access mainly lower-level skills; but others, for example, with multiple choice questions to assess inferential understanding may demand higher-level skills. Empirical studies have found considerable degrees of similarity between reading comprehension and listening comprehension (Buck, 1992 ; Petersen et al, 2020 ). Therefore, it can be inferred that different listening comprehension measures tap different cognitive processes, too.…”
Section: Literature Reviewmentioning
confidence: 99%